Antidiabetic medication use during pregnancy: an international utilization study - Øystein Karlstad; Jiong Li; Kari Furu; Helle Kieler; Hanne L Gulseth; Carolyn E Cesta; Helga Zoega; Jacqueline M Cohen; Laura Pazzagli; Brian T Bateman; Gabriella Bröms; Kristjana Einarsdóttir; et al. (BMJ Open Diabetes Research & Care)
Objective Diabetes in pregnancy and consequently the need for treatment with antidiabetic medication (ADM) has become increasingly prevalent. The prevalence and patterns of use of ADM in pregnancy from 2006 onward in seven different countries was assessed.Research design and methods Data sources included individually linked data from the nationwide health registers in Denmark (2006–2016), Finland (2006–2016), Iceland (2006–2012), Norway (2006–2015), Sweden (2006–2015), state-wide administrative and claims data for New South Wales, Australia (2006–2012) and two US insurance databases: Medicaid Analytic eXtract (MAX; 2006–2012, public) and IBM MarketScan (2012–2015, private). The prevalence of ADM use was calculated as the proportion of pregnancies with at least one filled prescription of an ADM in the 90 days before pregnancy or within the three trimesters of pregnancy.Results Prevalence of any ADM use in 5 279 231 pregnancies was 3% (n=147 999) and varied from under 2% (Denmark, Norway, and Sweden) to above 5% (Australia and US). Insulin was the most used ADM, and metformin was the most used oral hypoglycemic agent with increasing use over time in all countries. In 11.4%–62.5% of pregnancies with prepregnancy use, ADM (primarily metformin) was discontinued. When ADM treatment was initiated in late pregnancy for treatment of gestational diabetes mellitus, insulin was most often dispensed, except in the US, where glibenclamide was most often used.Conclusions Prevalence and patterns of use of ADM classes varied between countries and over time. While insulin remained the most common ADM used in pregnancy, metformin use increased significantly over the study period.